The impact of heavy truck electrification on greenhouse gas emissions in Ontario, Canada - Mehdi Ebrahimi; David S.-K. Ting; Rupp Carriveau; Hanna Maoh; Darryl Danelon (Transportation Engineering, 2024)
In this work, the new energy demand and greenhouse gas emissions that would be associated with heavy truck electrification in Ontario is evaluated. A new equation is derived to calculate the pollution-producing electricity generation based on the breakdown of the Ontario generation mosaic. Using this as a basis, for 4 scenarios of 5 %, 25 %, 50 % and 75 % of heavy-duty truck electrification, the Marginal Emission Factor (MEF) is calculated. This evaluation suggests that Ontario's peak demand in 2040 for the least and the most heavy-duty truck electrification scenarios can be up to 27.5 GW and 30.4 GW, respectively, compared to a baseline of 26.8 GW when assuming no heavy truck electrification condition. It is also forecasted that if the extra demand for electric trucks is supplied by clean renewable resources, the GHG emission reduction for 2040 can be as high as 0.9 MT, 4.3 MT, 8.6 MT and 12.9 MT GHG, respectively.